2016
DOI: 10.1038/srep20227
|View full text |Cite
|
Sign up to set email alerts
|

Human X-linked Intellectual Disability Factor CUL4B Is Required for Post-meiotic Sperm Development and Male Fertility

Abstract: In this study, we demonstrate that an E3-ubiquitin ligase associated with human X-linked intellectual disability, CUL4B, plays a crucial role in post-meiotic sperm development. Initially, Cul4bΔ/Y male mice were found to be sterile and exhibited a progressive loss in germ cells, thereby leading to oligoasthenospermia. Adult Cul4b mutant epididymides also contained very low numbers of mature spermatozoa, and these spermatazoa exhibited pronounced morphological abnormalities. In post-meiotic spermatids, CUL4B wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…Large number of E3 ligases have been identified that are expressed during mouse spermatogenesis with many of them are shown to be expressed highly or specifically in the testis 43 . Similarly, Cul4A and Cul4B have been shown to express highly in mouse testis 23 , 25 . The CUL4A and CUL4B exhibited complementary expression patterns in adult mouse testis, where CUL4A primarily expressed in spermatocytes during meiosis, while CUL4B was highly expressed in Sertoli cells, spermatogonia and spermatids 24 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Large number of E3 ligases have been identified that are expressed during mouse spermatogenesis with many of them are shown to be expressed highly or specifically in the testis 43 . Similarly, Cul4A and Cul4B have been shown to express highly in mouse testis 23 , 25 . The CUL4A and CUL4B exhibited complementary expression patterns in adult mouse testis, where CUL4A primarily expressed in spermatocytes during meiosis, while CUL4B was highly expressed in Sertoli cells, spermatogonia and spermatids 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Disruption of Cul4A caused male infertility because of the defective meiotic progression 24 , 25 . Whereas, the male infertility phenotype resulted from Cul4B deletion was due to abnormal post-meiotic sperm development 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In MSCs, they were larger and more spherical, while in adipocytes, an ellipsoid shape was observed. The occurrence of changes in the nuclear shape during differentiation and maturation is a well-known phenomenon (Skinner and Johnson 2017), with extreme examples concern lobulated nuclei in neutrophils (Carvalho et al 2015) or elongated nuclei in spermatids (Lin et al 2016). This suggests that changes in the nuclear shape and structure during cell specialization are related to the function and phenotype of the cell (Dahl et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…During mammalian spermiogenesis, most nucleosomal histones are removed and replaced by histone variants, transition proteins and subsequently protamines. [50][51][52][53] The process of histone-toprotamine replacement repackages the sperm genome to be at least 6-fold more compact than its somatic counterpart. 52 To evaluate whether histone replacement was affected in RNF8¡/¡ males and RAD6B¡/¡ males, we used immunofluorescence to assess the expression of testes-specific histone H2B (tH2B) during spermatogenesis.…”
Section: Rad6b-and Rnf8-deficient Male Mice Have Reduced Sperm Producmentioning
confidence: 99%